Note: In below samples, C or D cannot equal \(\displaystyle 1\)
We are assuming the ln values have been evaluated so no absolute value signs.
Case A
\(\displaystyle A \ln (C) \pm A\ln (C) = \)
\(\displaystyle 5\ln(9) - 5 \ln(9) = \)
\(\displaystyle 5\ln(9) + 5 \ln(9) = \)
Case B:
\(\displaystyle A \ln (C) \pm B\ln (C) = \)
\(\displaystyle 5\ln(9) - 4 \ln(9) = \)
\(\displaystyle 5\ln(9) + 4 \ln(9) = \)
Case C:
\(\displaystyle A \ln (C) \pm A\ln (D) = \)
\(\displaystyle 5\ln(6) - 5 \ln(2) = \)
\(\displaystyle 5\ln(6) + 5 \ln(2) = \)
Case D:
\(\displaystyle A \ln (C) \pm B\ln (D) = \)
\(\displaystyle 5\ln(4) - 3 \ln(5) = \)
\(\displaystyle 5\ln(4) + 3 \ln(5) = \)
We are assuming the ln values have been evaluated so no absolute value signs.
Case A
\(\displaystyle A \ln (C) \pm A\ln (C) = \)
\(\displaystyle 5\ln(9) - 5 \ln(9) = \)
\(\displaystyle 5\ln(9) + 5 \ln(9) = \)
Case B:
\(\displaystyle A \ln (C) \pm B\ln (C) = \)
\(\displaystyle 5\ln(9) - 4 \ln(9) = \)
\(\displaystyle 5\ln(9) + 4 \ln(9) = \)
Case C:
\(\displaystyle A \ln (C) \pm A\ln (D) = \)
\(\displaystyle 5\ln(6) - 5 \ln(2) = \)
\(\displaystyle 5\ln(6) + 5 \ln(2) = \)
Case D:
\(\displaystyle A \ln (C) \pm B\ln (D) = \)
\(\displaystyle 5\ln(4) - 3 \ln(5) = \)
\(\displaystyle 5\ln(4) + 3 \ln(5) = \)
Last edited: